PENGENALAN KOMPONEN KOMPUTER BERBASIS AUGMENTED REALITY PADA ANDROID DENGAN METODE SINGLE MARKER - Andreas, Nathanael; Suryantara, I Gusti Ngurah (Universitas Bunda Mulia, 2023)
Computers are one of the most popular electronic devices today. With the development of PC games and Esports in the world, computers are becoming more and more popular among young people today. Computers have many components that are needed as a support so that the computer can be used. At the education level, students are taught about the components in a computer. However, the introduction still uses images because it is difficult to introduce the components one by one. One way to easily introduce components on a computer is to use Augmented Reality technology. Augmented Reality allows users to be able to combine the virtual world, both 2D and 3D, with the real environment in real time. This application is based on Android and is built using the Unity3D Game Engine. The method used in developing this computer component recognition application is the single marker method and uses the FAST Corner Detection algorithm. In addition, application development will use the Multimedia Development Life Cycle (MDLC) method. The reason for making this computer component recognition application is so that it can be a tool to introduce computer components to students more attractively and make it easier for students to absorb the existing material. Based on the test results, the single marker method and the FAST Corner Detection algorithm were successfully implemented into the application. The application can run well on Android 5.1 to Android 10 with a minimum of 2GB RAM. The results of the single marker method test that the marker can be detected by the camera. Marker detection can be done on markers with a slope of 0° - 45°. The closest distance for marker detection is 4cm and the farthest distance for marker detection is 92cm. The results of the questionnaire on questions about the functionality of the application with a total of 30 respondents who were students of Class 12 Bunda Mulia School answered